Spectacularization of intimacy in bus iconography of the Colombian Caribbean from 2013 to 2023. (Encuentros, 2024)
This article is derived from the research Sign, symbol and language in the iconography of buses in the Colombian Caribbean1. It analyzes the spectacularization of the subject's intimacy represented in iconography that hangs from the bodies of public transportation buses. The aim is to know if these constitute representations of power, territory, history and the cultural identity of the subjects based on iconological communication. The methodological design is based on reviewing an inventory of more than 1,000 photographs recorded over a period of ten years in the main cities of the Colombian Caribbean, with the selection of a final sample of 15 iconography and the same number of semi-structured interviews with bus drivers and owners. The results are interpreted in the light of theorists such as Foucault, Cassirer, Habermas and Debord among others. Within the findings it is revealed that, in some cities, public space is being emptied of signs and symbols that make up the cultural identity of the subjects and replaced by iconic ones of commercial and institutional power.
Keywords: Iconology, iconography, Buses, representation, intimacy, spectacularization, Colombian Caribbean